Your research project : designing and planning your work - Walliman, Nicholas (Sage Publications, 2011)
"In the third edition of this bestselling book, you'll find everything you need to embark upon your research project and write your proposal with confidence...[this book] will guide you through the process of formulating a research question, choosing your research methods, planning your research, and writing your proposal"--P. [4] of cover.